RISK FACTORS FOR THE DEVELOPMENT OF GASTRIC CANCER: A SINGLE CENTER EXPERIENCE - Rančić, Andrija; Brzački, Vesna; Aleksandar, Popović; Marija, Topalović (Acta medicae Medianae, 2023)
Gastric cancer is the fourth most common cancer in the world with over a million new cases per year, and over 750,000 deaths caused by it. The highest incidence is recorded in Japan and China, Eastern Europe and South America, and the lowest is in Africa. The disease is 2 to 3 times more common within male population and people over 60 years of age, but this boundary shifts towards younger age. Five-year survival rate in European countries is 10 to 30%. This is a multifactorial disease and the most important risk factors are: Helicobacter pylori infection, smoking cigarettes, alcohol consumption, male gender, older age, reduced intake of vegetables and fruits, genetic predisposition, diabetes mellitus, etc. A prospective study was conducted on a selected population of 43 patients diagnosed with the two most common types of stomach cancer: adenocarcinoma and signet ring cell type cancer. Out of the total number of examinees, there were 32 male and 11 female patients, the average age of 68.83±9.26. Among all patients, 39.5% were smokers, 20.9% were alcohol consumers, 62.8% had Helicobacter pylori infection and 16.3% patients had diabetes mellitus. Analysis of the relationship between sex, age, smoking, alcohol intake and diabetes mellitus with the type of cancer did not show statistical significance. The frequency of Helicobacter pylori was statistically significantly different in relation to the type of cancer (p=0.007). In our study, there was no statistically significant difference between the male gender, the younger population, smokers, chronic alcohol consumers, and patients with diabetes mellitus and a certain type of cancer. Helicobacter pylori infection was found to be a key factor in the development of both types of gastric cancer. This research included a smaller sample of patients and it is necessary to examine a larger number of subjects in the future.